The influence of gamma-radiation on the form of Electronic spin resonance-line of F-centers in halite - Литовченко, А.С.; Полькова, Ю.С.; Сьомка, В.В.; Кузнєцова, О.Я. (Proceedings of National Aviation University (archive), 2005)
The form of Electronic spin resonance-line of F-centers in the halite structure depending on gamma-radiation dose (up to 100 MGy) and annealing temperature (up to 200 0C) of gamma-irradiated samples have been studied by the method of moments M2. It was shown that M2-value represented the dynamics of F-centers accumulation and recombination in the NaCl-structure. The obtained results are important for the development of prognosis method of halite radiation stability when using rock salt formations as candidates for creation the geological high-level radioactive waste repository.